Assessing resource and infrastructure disparities to strengthen Indian dairy sector - KALE, RAJIV BALIRAM; PONNUSAMY, K; CHAKRAVARTY, A K; SENDHIL, R; MOHAMMAD, ASIF (The Indian Journal of Animal Sciences, 2016)
The present study reveals the resource and infrastructure disparities of dairy development in India. The relative progress of the states in dairying was measured by multitude of developmental indicators. To get a lucid picture, a composite Dairy Progressiveness Index (DPI) with 20 indicators was developed for 16 states of India. Principal Component Analysis (PCA) was employed for the construction of DPI. As per the indices score, Punjab, Kerala, Haryana, Goa and Gujarat were categorized as highly dairy progressive states. Tamil Nadu, Rajasthan, Maharashtra, Andhra Pradesh, Karnataka and Uttar Pradesh were categorized as moderate dairy progressive states while West Bengal, Himachal Pradesh, Bihar, Madhya Pradesh and Odisha states were grouped as least dairy progressive states. The study implicates the strong need to develop organized marketing network along with reforms in dairy cooperatives as well as producer companies in Punjab, Haryana, Himachal Pradesh, Bihar, Madhya Pradesh and Odisha. Since fodder, pasture and irrigation resources in Himachal Pradesh, Andhra Pradesh, Madhya Pradesh, Odisha, Kerala and Gujarat are poor, policy intervention like restriction on export of oilseed cake and ban on harvesting using combine harvester without straw ripper, establishment of fodder bank network could address the fodder scarcity. Transfer of technologies such as hydroponics, azolla, silage, urea treatment, use of mineral mixtures to field in resource poor states need attention. Poor genetic potential in the low performing states demand proper breeding strategies, conservation and spread of elite indigenous breeds such as Sahiwal, Gir and Tharparkar. Improvement in veterinary infrastructure would reduce the imbalanced progress. The policy interventions on identified gaps would pave even development of dairy farming and reduce future demand gap.